Hamlet’s crisis of meaning, mental wellbeing and meaninglessness in the War on Terror - Pupavac, Vanessa (Pavilion Journals, 2008)
Drawing on Shakespeare, and in particular Hamlet's psychological crisis, this paper examines the relationship between emotions and meaning, a key theme in artistic work, but, it is argued, neglected in social psychology. Hamlet's psychological crisis is caused by the storng competing frameworks of meanings, which confronted individuals emerging from traditional society. Conversely the twenty-first century psychological crisis arguably relates to meaninglessness or the weakening of earlier sources of meaning. Studies exploring the crisis of meaning are applied to the War on Terror and international terrorism.